Platelet rich fibrin in regenerative dentistry : biological background and clinical indications - Miron, Richard J. (Richard John), 1983-; Choukroun, Joseph, 1952- (John Wiley & Sons Ltd, 2017)
The first book devoted exclusively to the subject, Platelet Rich Fibrin in Regenerative Dentistry offers comprehensive, evidence-based coverage of the biological basis and clinical applications of PRF in dentistry. Co-edited by a leading researcher in tissue regeneration and the inventor of the PRF technique, it brings together original contributions from expert international researchers and clinicians. Chapters cover the biological foundation of PRF before addressing specific uses of the technology within clinical dentistry. Topics describe the use of PRF in many dental applications, including extraction socket management, sinus lifting procedures, root coverage, periodontal regeneration, soft tissue healing around implants, guided bone regeneration, and facial esthetics. The text is supplemented with color photographs and explanatory illustrations throughout. Platelet Rich Fibrin in Regenerative Dentistry: Biological Background and Clinical Indications is an indispensable professional resource for periodontists, oral surgeons and oral and maxillofacial surgeons, as well as general dentists who use PRF or are interested in introducing it into their practices. It is also an excellent reference for undergraduate and postgraduate dental students.